Conversion of solar radiation into heat through carbon nanotubes with potential industrial applications - Huera Solórzano, Ariel Alexander (2022)
Carbon nanostructures and specifically carbon nanotubes have become of high importance due their outstanding properties for many different areas in science and engineering. In this work has been identified an application related to their ultra-high absorbance in the region of visible and infrared light. This property can be used to harvest solar energy to e.g. heat water for industrial processes, a path to reduce fuel consumption. The presence work successfully shows a new technique to fabricate MWCNTs directly on an activated aluminum surface using the CVD procedure. Low-temperature synthesis was achieved around 650 [°C] and their characterization was made by using Raman spectroscopy that confirms the presence of MWCNTs with their main signature at 1346 [cm^-1], 1582 [cm^-1], and 2692 [cm^-1] for D-band, G-band, and 2D-band correspondingly. Scanning electron microscopy was used to explore the synthesized material and morphology presenting cotton-like structures deposited on the Al surface. XPS proved the presence of sp2, sp3 binding carbon hybridization related with carbon nanotubes and amorphous carbon structures. Finally, the fabricated materials were tested under direct sun exposure. The results show that our device heats, on average, 3.44 [°C] more than other materials compared. We perform an exergy analysis of the temperature contrasts achieved and results are very promising for up-scaling surface areas. Temperature contrasts can be increased by improving the CNT coverage and the heat capacities of the base substrate used. This research work opens the possibilities to use this material for several applications regarding the renewable energies that can be done in Ecuador in the very shortly.